Marvell's Allusions. Issue 1 (14th September 2020) - McGrath, Patrick J.
Abstract : This article attempts to define Marvell's allusions and offers six characteristic features of his allusivity to do so: indirectness, similitude, denaturalization/adaptation, ironic contrast, criticism, and meaningfulness. Based on these features, the article maintains that the allusion is a particularly intellective, intricate, and intentional category of Marvellian intertextuality. It compares these qualities with the Marvellian echo, whose dubious intentionality, greater visibility, and shallower meaning markedly contrast with the allusion. While the moment of readerly recognition frequently exhausts the meaning of an echo, allusions contain depths that readers must laboriously sound. In short, the article attempts to introduce more precision and accuracy into a body of scholarship that frequently treats Marvell's echoes and allusions as interchangeable.